Detached commercial architecture - Cruz, António (Hong Kong : Design Media Publishing, 2014)
The book focuses on the planning and design of commercial architecture that belongs to one brand. Nowadays companies tend to build single buildings for their own brands to highlight their brand value and characters. The book includes more than 20 amazing projects from different countries with various styles. These projects interpret basic architectural vocabulary of detached commercial buildings and demonstrate design principles comprehensively. Each project has its unique characteristics: some use unique forms and skillful colour combination to give unique features to the buildings, some emphasise integration with environment, some place the buildings in historical and cultural inheritance, some use new materials and reasonable texture to reinforce the expression, some focus on the use functions, some conform to contemporary requirements of low carbon and energy saving...The content is divided into four parts: architecture with shopping environment, architectural forms and materials, color, and eco-architecture. The projects are presented in combination with design guidelines, depicting the international status of detached commercial architecture now.
engineering bookfair2016
Keywords: Stores, Retail -- Design and construction; Branding (Marketing)